A practical approach to MIL-STD-1553 bus transceiver analog front end with discrete components and IC design under UMC130NM process - Soltani, Amin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
This thesis deals with the research and built of a commercially operational MILSTD- 1553 Bus Transceiver Analog front end in both PCB with discrete elements and CMOS IC design in Cadence under umc130nm technology which are used in various Avionics and aerospace applications. Although the functional block diagram of a bus transceiver is depicted and used in the literature widely, nevertheless, there is little close to none information on how one should implement such circuit. Companies such as Sital, Cobham, Holt integrated and DDC to name a few, build and commercially use 1553 BUS families without disclosing the schematic information of the circuit. This leaves us to build the receiver and the transmitter almost from scratch by bene ting from other line/transformer driving circuitry ideas used in LVDS [1], modem lines and other di erential signaling methods [2]. The inductive and resonance behavior of the isolation transformer winding is widely discussed to be able to generate the optimum method for driving the terminals of the transceiver to meet the speci c requirements dictated by 1553 standards back in 1973 by U.S.Air Force [3]. Also analytical solutions are presented for the method developed to help understand how the electrical requirements stated by 1553 can be tuned in the circuit. Altium PCB and Cadence layout design are shown with in-depth system testing and post layout simulations. The PCB board is manufactured and is successfully operational. The points of improvement on the board, backed up with reasoning, are discussed.
Keywords: Airplanes -- Electronic equipment -- Design and construction.; Standards, Military -- Electronic equipment -- Design and construction